2017
DOI: 10.7759/cureus.1040
|View full text |Cite
|
Sign up to set email alerts
|

The Use of WhatsApp Smartphone Messaging Improves Communication Efficiency within an Orthopaedic Surgery Team

Abstract: Introduction: Effective and timely communication is important for any surgical specialty to function. The use of smartphones is prevalent amongst doctors. Numerous smartphone applications offer the potential for fast and cost-effective communication. WhatsApp is a commonly used application that is free, easy to use, and capable of text and multimedia messaging. We report on the use of WhatsApp over a six month period in our unit.Materials and Methods: WhatsApp communication between non-consultant members of an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
44
0
5

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(56 citation statements)
references
References 9 publications
0
44
0
5
Order By: Relevance
“…5 A surgical program has very unique communication needs that are amenable to the adoption of modern means, such as Webbased surveying. Instant multimedia messaging is an obvious replacement for the pager, given the ubiquitous nature of smartphones, and it can stratify calls based on clinical need.…”
Section: Resultsmentioning
confidence: 99%
“…5 A surgical program has very unique communication needs that are amenable to the adoption of modern means, such as Webbased surveying. Instant multimedia messaging is an obvious replacement for the pager, given the ubiquitous nature of smartphones, and it can stratify calls based on clinical need.…”
Section: Resultsmentioning
confidence: 99%
“…Smartphones also serve as an important means of medical collaboration and consultation and are commonly used by residents during on‐call shifts when the input of an attending physician can significantly contribute to patient management . Previous studies have demonstrated the efficacy of several messaging and web‐based applications such as WhatsApp Messenger (Facebook Inc, California, USA) in improving the care of surgical patients and the interpretation of medical diagnostic tests, such as electrocardiograms .…”
Section: Introductionmentioning
confidence: 99%
“…Bir iletişim yazılımı programı olan WhatsApp, 2009 yılında geliştirildi ve günden güne sağlık çalışanlarının günlük rutinlerinde kullanılmaya başla-dı (1) . Klinik uygulamada mobil iletişim teknolojileri çoğunlukla; hastalar ve çalışma arkadaşlarıyla iletişim, konsültasyon, hasta takibi, ekip arası toplu mesajlaşma ve telekonferans amacıyla kullanılmaktadır (1)(2)(3)(4)(5)(6)(7)(8)(9) . WhatsApp'ın tıp dünyasında kullanımında sağla-dığı pek çok avantajın yanı sıra bazı potansiyel riskleri de mevcuttur.…”
Section: Introductionunclassified